2012
DOI: 10.1016/j.jcgg.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting falls among Egyptian nursing home residents: A 1-year longitudinal study

Abstract: a b s t r a c tBackground/Purpose: Falls and their related complications are serious health problems among the institutionalized older population. This study aimed to evaluate the incidence of falls and the risk factors among nursing home residents in Cairo, Egypt. Methods: A one-year prospective cohort study was done in three nursing homes in Cairo. Overall, 84 residents aged over 60 years participated in this study. Baseline demographic characteristics and results of comprehensive geriatric assessments, e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Therefore, a minority of older people was considered robust as per the same criteria, indicating that most of them had already progressed to initial or advanced frailty states. Some authors [24][25][26][27][28]31,32 corroborated the findings obtained herein, reporting combined frailty and pre-frailty prevalences between 91.1 and 96.3%. However, El Zoghbi et al 27 and Khater & Mousa 28 , in studies carried out in Lebanon and Egypt, respectively, encountered lower proportions of frail or pre-frail older people, when observing younger individuals.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, a minority of older people was considered robust as per the same criteria, indicating that most of them had already progressed to initial or advanced frailty states. Some authors [24][25][26][27][28]31,32 corroborated the findings obtained herein, reporting combined frailty and pre-frailty prevalences between 91.1 and 96.3%. However, El Zoghbi et al 27 and Khater & Mousa 28 , in studies carried out in Lebanon and Egypt, respectively, encountered lower proportions of frail or pre-frail older people, when observing younger individuals.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests a higher prevalence of frailty when compared to other studies that used the criteria of Fried et al (2001) that were conducted on institutionalized older people of Brazil and developed countries, and reported frailty rates between 23 and 69% [24][25][26] . Other studies that used other instruments of measurement, such as the Canadian Study of Health and Aging-Clinical Frailty Scale, osteoporotic fractures frailty index, the Groningen Frailty Indicator or the Edmonton Frail Scale, have reported that this issue affects between 35 and 77% [27][28][29][30][31] . Although these works used the same similar criteria, none of them analyzed individuals with cognitive impairment or without gait capacity.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, another case control among residents of nursing homes in Egypt found no difference in the number of prescribed drugs between fallers and nonfallers; however, fallers were older than nonfallers, which could add underlying risk rather than the number of the prescribed drugs.…”
Section: Discussionmentioning
confidence: 99%
“…First aid is the immediate and temporary help given to a victim of injury or sudden illness until appropriate medical help arrives, or the victim is seen by a healthcare provider (Khater & Mousa, 2012) The most important thing in first aid is to notice the situation and to call for help. Calling for help is a simple thing to do, but also the most important thing to ensure that the elderly will get professional help.…”
Section: Introductionmentioning
confidence: 99%